Ethnic language and bilingualism: The acquisition of karajá as a second language - Pereira de Oliveira, Caroline; Vicente Ferreira, Rogério; Hagemeyer Burgo, Vanessa (Revista Linguagem & Ensino, 2020)
This work aims to discuss the acquisition process of ethnic language as a second language in the community of Buridina in Aruanã – Goiás – Brazil. By drawing attention to bilingualism, we observe the practice of alternately using two languages: some people speak Portuguese as their first language while others speak Karajá. We also intend to highlight the actions promoted by Karajá people in order to preserve their own language, culture, values, tradition and knowledge, bearing in mind their need to interact with non-indigenous people within an indigenous society whose predominant language is Portuguese for many inhabitants. Our theoretical framework is based on studies concerning bilingualism and second language acquisition related to indigenous studies. According to the findings, the acquisition of Karajá as a second language, in Buridina, occurs both in social specialized spaces as well as in social daily life contexts, comprising activities that value cultural and intercultural aspects of that community’s language.